The impact of energy alignment and interfacial recombination on the internal and external open-circuit voltage of perovskite solar cells. Issue 9 (22nd July 2019) - Stolterfoht, Martin; Caprioglio, Pietro; Wolff, Christian M.; Márquez, José A.; Nordmann, Joleik; Zhang, Shanshan; Rothhardt, Daniel; Hörmann, Ulrich; Amir, Yohai; Redinger, Alex; Kegelmann, Lukas; Zu, Fengshuo; et al.
Abstract : We quantify recombination losses in the bulk and interfaces for different perovskite compositions and popular charge transport layers. Abstract : Charge transport layers (CTLs) are key components of diffusion controlled perovskite solar cells, however, they can induce additional non-radiative recombination pathways which limit the open circuit voltage ( V OC ) of the cell. In order to realize the full thermodynamic potential of the perovskite absorber, both the electron and hole transport layer (ETL/HTL) need to be as selective as possible. By measuring the photoluminescence yield of perovskite/CTL heterojunctions, we quantify the non-radiative interfacial recombination currents in pin - and nip -type cells including high efficiency devices (21.4%). Our study comprises a wide range of commonly used CTLs, including various hole-transporting polymers, spiro-OMeTAD, metal oxides and fullerenes. We find that all studied CTLs limit the V OC by inducing an additional non-radiative recombination current that is in most cases substantially larger than the loss in the neat perovskite and that the least-selective interface sets the upper limit for the V OC of the device. Importantly, the V OC equals the internal quasi-Fermi level splitting (QFLS) in the absorber layer only in high efficiency cells, while in poor performing devices, the V OC is substantially lower than the QFLS. Using ultraviolet photoelectron spectroscopy and differential charging capacitance experiments we show that this is due to an energy level mis-alignment at the p -interface. The findings are corroborated by rigorous device simulations which outline important considerations to maximize the V OC . This work highlights that the challenge to suppress non-radiative recombination losses in perovskite cells on their way to the radiative limit lies in proper energy level alignment and in suppression of defect recombination at the interfaces.